Evaluation of the immune response following a short oral vaccination schedule with hepatitis B antigen encapsulated into alginate-coated chitosan nanoparticles - Borges, Olga (2007)
The purpose of this work was to assess the ability of recombinant hepatitis B vaccine, encapsulated in alginate-coated chitosan nanoparticles, to induce local and systemic immune responses following oral vaccination. The antigen was administered either alone or in combination with the immunopotentiator, synthetic oligodeoxynucleotide containing immunostimulatory CpG motif (CpG ODN) as adjuvant, and associated or not with the alginate-coated chitosan nanoparticles. After two immunizations the group I (HBsAg associated with nanoparticles) and the group VI (HBsAg and CpG, both associated with nanoparticles) showed enhanced immune responses. Both groups showed significant higher values of the CD69 expression in CD4+ and CD8+ T-lymphocytes and lower values of this marker in B lymphocytes. Moreover, a strongest proliferative response of the splenocytes, ex vivo stimulated with concanavalin A, was observed in the same groups. Although with a presence of non-responder mice within the groups, only mice of the groups I and VI elicited the generation of anti-HBsAg antibodies detected in serum (IgG) and in the intestinal washings (sIgA). The results demonstrated that coated chitosan nanoparticles might have potential for being used as a deliver system for oral vaccination with the recombinant hepatitis B surface antigen.